Allele-defined genome of the autopolyploid sugarcane Saccharum spontaneum L. (November 2018) - Zhang, Jisen; Zhang, Xingtan; Tang, Haibao; Zhang, Qing; Hua, Xiuting; Ma, Xiaokai; Zhu, Fan; Jones, Tyler; Zhu, Xinguang; Bowers, John; Wai, Ching; Zheng, Chunfang; et al.
Abstract Modern sugarcanes are polyploid interspecific hybrids, combining high sugar content fromSaccharum officinarum with hardiness, disease resistance and ratooning ofSaccharum spontaneum . Sequencing of a haploidS. spontaneum, AP85-441, facilitated the assembly of 32 pseudo-chromosomes comprising 8 homologous groups of 4 members each, bearing 35, 525 genes with alleles defined. The reduction of basic chromosome number from 10 to 8 inS. spontaneum was caused by fissions of 2 ancestral chromosomes followed by translocations to 4 chromosomes. Surprisingly, 80% of nucleotide binding site-encoding genes associated with disease resistance are located in 4 rearranged chromosomes and 51% of those in rearranged regions. Resequencing of 64S. spontaneum genomes identified balancing selection in rearranged regions, maintaining their diversity. IntrogressedS. spontaneum chromosomes in modern sugarcanes are randomly distributed in AP85-441 genome, indicating random recombination among homologs in differentS. spontaneum accessions. The allele-definedSaccharum genome offers new knowledge and resources to accelerate sugarcane improvement. Sequencing of haploid sugarcane, Saccharum spontaneum, allows assembly of a prototypical version of the sugarcane chromosome set. This new reference genome will serve as a resource to accelerate sugarcane improvement.